Placemaking Analysis on Improving The Quality of Merjosari Park Public Space - Izza, Aulia Nuraqiqotul; Ardiansyah, Nurrama Faris; Sadewa, Rama Dirgi; Maulana, Edwin; Syafi'i, Nurohman; Kusumadewi, Tarranita (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
Merjosari Park has recently experienced significant quality degradation due to prolonged neglect and insufficient maintenance. This study aims to assess the public space quality of Merjosari Park and analyze it based on placemaking principles. A descriptive quantitative methodology was employed, involving the identification of phenomena and environmental issues affecting public space quality, followed by numerical assessments derived from community perceptions. The study evaluated aspects of placemaking—including Uses and Activities, Access and Linkages, Comfort and Image, and Sociability. The analysis revealed a score of 125, with the highest contributions from Comfort and Image elements, such as user comfort, safety, cleanliness, and functionality. Despite being classified as good quality, the park's score sits at the lower threshold of this category. The study concludes that Merjosari Park requires targeted improvements to achieve higher quality standards and offers recommendations for development.